L'image manipulée : considérations sur une mosaïque de Sainte-Sophie - Tania Kambourova (Images Re-Vues)
The mosaic of Constantine IX and Zoe in the south gallery of Saint Sophia in Constantinople is the centre of our attention. The inscriptions and persons depicted in this mosaic have visibly been retouched. Contrary to the prevailing opinion we prove the mosaic “of Zoe” dates from before the Empress came to power; for her inscription has visibly been retouched and does not correspond to the characters in the original inscription above the masculine figure, now Constantine IX. A hypothesis is formed on the predecessors’ possible identities. The final reflections give an explanation for the imperial gifts.